Pengaruh Promosi Islami dan Kualitas Pelayanan Islami Terhadap Keputusan Nasabah Memilih BMT Hasanah: (Studi Kasus Di Bmt Hasanah Kantor Cabang Sambit) - Saba' Firdaus, Bilqis Ratu (Fakultas Syari'ah Institut Agama Islam Riyadlatul Mujahidin Ngabar (IAIRM) Ponorogo., 2022)
The Effect of Islamic Promotion and Islamic Service Quality on Customer Decisions to Choose BMT Hasanah (Case study at BMT Hasanah, Sambit branch office). This study aims to (1) Identify and analyze the effect of Islamic promotion on customer decisions to choose BMT Hasanah, (2) Identify and analyze the quality of Islamic services on customer decisions to choose BMT Hasanah, (3) Identify and analyze the effect of Islamic promotion and Islamic service quality on customer's decision to choose BMT Hasanah. This type of research is quantitative research, using multiple linear analysis to analyze data and test hypotheses using the IBM SPSS version 23 application. This study has two independent variables, namely Islamic promotion and Islamic service quality, and one dependent variable, namely the customer's decision to choose BMT Hasanah. Data obtained from questionnaires that have been distributed to 60 respondents, namely BMT Hasanah customers who were selected through technique simple random sampling and measured by a likert scale. Based on the analysis performed by the researchers, it can be concluded that the partial test promotion variables Islami does not significantly influence the customer's decision choosing BMT Hasanah it is evidenced by t value the (0.551) <t table (2.002), so that the research hypothesis Ha rejected and H0 is accepted. Partial assay results Islami service quality variables showed a significant effect on the customer's decision to choose BMT Hasanah t value (4.980)> t table (2.002), so that the research hypothesis H0 is rejected and Ha accepted. The simultaneous test results of Islamic promotion variables and Islamic service quality on the customer's decision to choose BMT Hasanah show a significant effect, this is indicated by the value calculated (22.832> f table (3.18). So that the research hypothesis H0 is rejected and Ha is accepted. The value of Adjusted R Square is 0.425 or 42.5%, meaning that the Islamic promotion variable and Islamic service quality have an influence on the customer's decision to choose BMT Hasanah by 42.5%, while the remaining 57.5% is influenced by other variables not included in the research variable.